2002
DOI: 10.1007/s100670200129
|View full text |Cite
|
Sign up to set email alerts
|

Large Vessel Arteritis Associated with Human Herpesvirus 6 Infections

Abstract: A 9-month-old boy presented with chronic arteritis of the aorta and its major branches. The clinical manifestations at onset of his illness were compatible with those of Kawasaki syndrome. However, the febrile period lasted for 2 months despite various immunosuppressive therapies, and the levels of C-reactive protein remain high 18 months after onset. Elevated circulating immune complexes, decreased serum complement levels, hypergammaglobulinaemia and monoclonal gammopathy were observed. Active HHV-6 infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…1 Although certain HLA-DR alleles are correlated with GCA, 2 genetic factors are insufficient to explain the marked variation in geographic prevalence 3 and the temporal fluctuation in the incidence of the disease. 1 Different findings suggest that infectious agents may be involved in the pathogenesis of the disease: parvovirus B19 (B19), 4 5 human herpes virus 6 (HHV-6), 6 and varicella zoster virus (VZV). 7 8 This study aimed at determining B19, VZV, and HHV-6 DNA prevalence and viral loads in temporal artery biopsy (TAB) specimens of patients with GCA, to analyse the hypothesis that an environmental factor may have a role in the pathogenesis of GCA.…”
mentioning
confidence: 99%
“…1 Although certain HLA-DR alleles are correlated with GCA, 2 genetic factors are insufficient to explain the marked variation in geographic prevalence 3 and the temporal fluctuation in the incidence of the disease. 1 Different findings suggest that infectious agents may be involved in the pathogenesis of the disease: parvovirus B19 (B19), 4 5 human herpes virus 6 (HHV-6), 6 and varicella zoster virus (VZV). 7 8 This study aimed at determining B19, VZV, and HHV-6 DNA prevalence and viral loads in temporal artery biopsy (TAB) specimens of patients with GCA, to analyse the hypothesis that an environmental factor may have a role in the pathogenesis of GCA.…”
mentioning
confidence: 99%
“…HHV‐6 infection of the cardiovascular system in infancy appears to be rare. Two cases of fetal acute myocarditis have been reported in Japan [Fukae et al, 2000; Rohayem et al, 2001; Yoshikawa et al, 2001; Toyabe et al, 2002; Chang et al, 2009]. DNA and serologic studies confirmed that the cause was primary HHV‐6B infection.…”
Section: Hhv‐6 Myocarditis Cardiomyopathy and Arterial Dysfunctionmentioning
confidence: 97%
“…4 HHV-6'nın akut apandisit ve aortta kronik arterite yol açtığına dair yayınlar da bildirilmiştir. 26,27 Ayrıca, HHV-6 reaktivasyonu ile skleroderma arasında güçlü bir ilişki olduğu öne sürülmekte-dir. 28 HHV-6 için tanısal testler seroloji, kültür, immünohistokimya ve nükleik asit incelemelerinden ibarettir.…”
Section: Human Herpes Vi̇rüs-6unclassified